An investigation into the patterns and trends of injuries in community assault cases at the Tygerberg Forensic Pathology Facility over a 10-year period from 1 January 2003 to 31 December 2012 - Herbst, Celeste Ingrid (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2015.